Computational analysis of flow field characteristics of a liquid rocket unshrouded impeller. Issue 3 (March 2019) - Negishi, H; Ohno, S; Fukuda, T; Ogawa, Y
Abstract: The unshrouded impeller applicable to liquid rocket pumps is a new technology compared to the conventional shrouded impeller widely used in existing liquid rocket engines. Although many past studies have investigated head/suction performance, the rotordynamic and axial forces acting on unshrouded impellers, the detailed flow field in unshrouded impellers, and particularly the influence of the compressibility of hydrogen have yet to be discussed. This paper describes the application of three-dimensional compressible Reynolds-averaged Navier-Stokes simulations to investigate the detailed flow field in a liquid rocket hydrogen pump with an unshrouded impeller. First, the computed results were validated relative to the experimental results obtained in the LE-X hydrogen pump test. Then, the detailed flow field was investigated by comparing the computed results at two different flow coefficients. The computed results agreed well with the experimental results, and revealed several key features of the flow field in the unshrouded impeller.